Residue of organochlorinated pesticides (OCPs) in some organisms of the tidal flats in the northern part of Vietnam - Trang, Cao Thi Thu; Thung, Do Cong; Kha, Pham Thi; Nam, Le Van; Nghi, Duong Thanh (Vietnam Journal of Marine Science and Technology, 2019)
Organochlorinated pesticides (OCPs) had been used widely in agriculture for protecting crop, eliminating insects. However, OCPs are banned in most countries because of their toxicity, long persistence and bio-accumulation. They are listed in carcinogen group and POP group (Persistent organic pollutants). In Vietnam, OCPs were banned in 1990s, but their residues are still found in the environments, including seawater, sediment and organisms. This paper presents the survey data of residues of OCPs in some organisms living in tidal flats in the northern part of Vietnam during the year 2013–2014. The results show that the total residue of OCPs in shellfish ranged from 5.57 µg/kg to 116.04 µg/kg dry weight. Compared with the American Guide for mollusk shellfish (2007), it is found that the organisms living in the tidal flats were not polluted by OCPs. However, these compounds can be accumulated in fat tissue even in very low concentration. Therefore, their presence in organism is alarming